Hyperglycemia, prognosis marker of adverse events in heart attack - Yudit García Cairo; Claudio M. González Rodríguez; Félix R. Jorrín Román; Francisco J. Valladares Carvajal; Juan J. Navarro López; Suleidy Castillo Fernández (ECIMED, 2014)
Introduction:Hyperglycemia on admission in patient with acute coronary syndrome is common, considered bad marker of clinical evolution and death.Objective:To value the use of admission glycemia like prognosis factor of adverse events in patient with heart attack.Method:Descriptive study and longitudinal prospective. 246 patients were included with heart attack admitted in Cienfuegoshospital and their evolution was continued during 30 days. It was determined as point of a very best cut for the mortality at admission glycemia ≥ 7,1mmol/l by means of the curve ROC and one carries out analysis logistics regression toidentify independent predictors of death.Results:The patients with glycemia ≥ 7,1mmol/l prevailed the diabetes, tachycardia,killip≥II, inferior localization, small ejectionfraction and bigger incidence of adverse events (60% versus 2%, p=0,000) as heart failure(30% versus 15%; p =0,001), malign ventricular arrhythmias (23% versus 4%; p = 0,000) and death(15% versus 3%; p = 0,001), with smaller survival regarding the patients with glycemia <7,1mmol/l(85,5% in contrast with 96,6%). Age and ejection fraction wereindependent predictors of death in the multivariate analysis.Conclusions:In patient with myocardial infarction thehyperglycemia to the entrance, with a cut point ≥7,1mmol/l, predicts a short term increment of adverse events, although it was not independent predictor of death